Solid electrolyte, all-solid-state flexible stretchable electrochromic device and preparation and application of all-solid-state flexible stretchable electrochromic device
By using solid electrolytes designed with polyurethane materials, curvature limitation and stability problems of electrochromic devices in wearable and adaptive camouflage applications are solved, and high-performance electrochromic devices are achieved, suitable for a variety of application scenarios.
Patent Information
- Application Number
- CN202411834719.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-04-04
AI Technical Summary
Existing electrochromic devices are limited by high curvature in wearable and adaptive camouflage applications, and the low conductivity and poor interface contact of solid electrolytes affect the stability and service life of the device.
Polyurethane materials are used as solid electrolytes, and chain extenders are introduced through the combination of diisocyanate, polyol and lithium salts to improve the ionic conductivity and mechanical properties of the material, and a dynamic hydrogen bond cross-linking network is constructed through molecular design.
It realizes high adhesion, environmental stability and versatility of solid electrolytes, and improves the stability, service life and application breadth of electrochromic devices, especially in the fields of wearable and adaptive camouflage.
Smart Images

Figure CN119758638A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of electrolyte materials, and in particular relates to a solid electrolyte, an all-solid-state flexible stretchable electrochromic device, and preparation and application thereof. Background Art
[0002] Electrochromism is a stable, reversible change in color and transparency of a material under the action of an external electric field. Electrochromic devices made of electrochromic materials generally include a transparent conductive layer, an electrochromic layer, an electrolyte layer, etc. Electrochromic devices are widely used in the fields of automobiles, aerospace, smart electronic displays, construction, and wearable devices. At present, wearable electrochromic devices have attracted widespread attention due to their diverse shapes and strong adaptability, but production technology and device materials limit the application of wearable electrochromic devices. At present, electrochromism is developing towards all-solid-state and intelligent. All-solid-state electrochromic devices have excellent stability and are safer during use.
[0003] Electrolytes in electrochromic devices can be divided into three types: liquid electrolytes, gel electrolytes, and liquid electrolytes. Liquid electrolytes are prone to leakage and are not resistant to low temperatures, which affects the service life and application range of electrochromic devices. Gel electrolytes have poor mechanical strength. In contrast, solid electrolytes are not easy to leak, are safer, and the structure of solid-state electrochromic devices is more stable. However, solid electrolytes have low conductivity and poor interface contact, which affects the stability and service life of electrochromic devices. Polyurethane material is a polymer with a two-phase structure of soft segments and hard segments. The hard segment provides mechanical strength for polyurethane, which keeps the mechanical properties of the electrolyte stable. The soft segment provides flexibility for polyurethane. Through molecular regulation, polyurethane electrolytes have good ionic conductivity and mechanical properties. Polyurethane materials perfectly meet the needs of electrolyte matrices and have broad application prospects in the field of wearable electrochromic devices.
[0004] Existing electrochromic devices are mostly limited to large curvatures, which restricts their application in wearable and adaptive camouflage. Summary of the invention
[0005] The technical problem to be solved by the present invention is to provide a solid electrolyte, an all-solid-state flexible stretchable electrochromic device and the preparation and application thereof.
[0006] The present invention provides a method for preparing a solid electrolyte, comprising:
[0007] (1) mixing a diisocyanate, a catalyst, and an organic solvent to obtain a mixed solution;
[0008] (2) mixing the mixed solution of step (1), polyol and lithium salt, and reacting them to obtain a prepolymer;
[0009] (3) A chain extender is added to the prepolymer of step (2) to react, and then the solvent is removed to obtain a solid electrolyte.
[0010] Preferably, in step (1), the diisocyanate is one or more of isophorone diisocyanate and hexamethylene diisocyanate; the catalyst is dibutyltin dilaurate; and the organic solvent is N,N'-dimethylacetamide.
[0011] Preferably, in step (2), the polyol is one or more of polytetrahydrofuran, polyethylene glycol, and polyethylene oxide; the lithium salt is one or more of lithium bis(trifluoromethylsulfonyl)imide, lithium difluoromethylsulfonylimide, and lithium perchlorate;
[0012] Preferably, in step (2), the polyol and the lithium salt are pre-treated, wherein the pre-treatment is vacuum drying to remove moisture.
[0013] Preferably, the structural formula of the chain extender in step (3) is:
[0014] Wherein R1 and R2 are selected from one or more of amino, carbonyl, carboxyl, and Upy;
[0015] Preferably, the molar ratio of polyol to chain extender is 1:(1-4).
[0016] Furthermore, the chain extender is 2-amino-2-methyl-1,3-propanediol.
[0017] Further, the molar ratio of the polyol to the chain extender is 1:1, 1:2 or 1:3.
[0018] Preferably, the molar ratio of the polyol to the diisocyanate is 1:(1-4); the catalyst accounts for 0.1wt%-0.9wt% of the total mass of the monomers (diisocyanate, polyol and chain extender); and the lithium salt content is 20wt%-60wt% of the total mass of the monomers (diisocyanate, polyol and chain extender).
[0019] Furthermore, the lithium salt accounts for 30% to 50% of the total mass of the monomer.
[0020] Furthermore, the molar ratio of the polyol to the diisocyanate is 1:1, 1:2 or 1:3.
[0021] Furthermore, the catalyst accounts for 0.4wt% to 0.7wt% of the total mass.
[0022] Preferably, the reaction in step (2) is carried out under protective gas conditions with stirring at 50-90° C. for 2-5 hours;
[0023] The chain extender is added in step (3) by adding a chain extender solution, such as dissolving the chain extender in an organic solvent and then adding the solution.
[0024] Preferably, the reaction in step (3) is as follows: stirring at 40-60°C for 2-5h, then heating to 80-90°C and stirring for 3-6h.
[0025] The present invention provides an electrochromic device, which comprises an electrochromic unit, a solid electrolyte prepared by the method, and a fabric substrate; wherein the solid electrolyte is arranged between the electrochromic unit and the fabric substrate.
[0026] The plurality of electrochromic units are connected by conductors and integrated on the surface of the substrate; the electrochromic layers of the electrochromic units on the surface of the substrate may be the same or different, and the electrochromic units may be arranged according to settings.
[0027] The number of integrated electrochromic units is more than 10, and furthermore is 30-100.
[0028] The electrochromic unit comprises in sequence a transparent conductive layer, an electrochromic layer, a solid electrolyte layer prepared by the method, and a transparent counter electrode layer.
[0029] The electrochromic layer is one or more of polythiophene, polyaniline and polypyrrole; the electrochromic unit area is 1-9cm 2 .
[0030] The invention provides a method for preparing an electrochromic device, comprising: stacking electrochromic units, solid electrolytes and fabrics, and then hot pressing to obtain the electrochromic units; wherein the electrochromic units are arranged in a set manner.
[0031] The electrochromic units are arranged in a regular pattern.
[0032] Furthermore, the hot pressing temperature is 50-100° C., and the hot pressing time is 30-120 s.
[0033] The present invention provides an application of the electrochromic device in the fields of wearable, information display and adaptive camouflage.
[0034] In order to meet the requirements of coordinated ion conduction ability and mechanical properties, a polyether polyurethane elastomer was designed and synthesized. Polyether polyols were selected as soft segments, which have good lithium salt dissociation ability. By introducing ether bonds, the interaction between polyurethane and lithium salt was increased, and the ionic conductivity was improved; aliphatic diisocyanates were selected as polyurethane hard segments, which can improve the mechanical properties of polyurethane while ensuring the transmittance. The functional groups in the chain extender can polymerize with the -NCO group to generate carbamate or allophanate, or can form hydrogen bonds with carbamate or allophanate to construct a double network polyurethane elastomer material with dynamic hydrogen bond crosslinking and chemical crosslinking as a solid electrolyte. Through molecular design, the ionic conductivity of the polyurethane electrolyte meets the requirements of electrochromism, and the excellent adhesion performance of the polyurethane electrolyte improves the stability and service life of the electrochromic device while improving the interfacial ion transmission performance.
[0035] Beneficial Effects
[0036] The solid electrolyte prepared by the method of the present invention has excellent adhesion performance and high environmental stability, and the electrochromic fabric has rich colors, controllable pattern shapes and areas, and is widely used.
[0037] The present invention uses three colors to achieve a variety of pattern designs. The electrochromic unit has a small area, and 30 to 100 electrochromic units can be arranged on the glove. The number is large, and the designed pattern is precise. The pattern can be designed according to the background to achieve the purpose of adaptive camouflage.
[0038] The multi-color blocks of the color-changing fabric can achieve rich electrochromic displays. The solid electrolyte has multiple hydrogen bonds, high adhesion, adaptability to environmental temperature and self-healing properties. The electrochromic device has the advantages of fast response, good stability and deformability. The multi-color block arrangement shows excellent environmental adaptability and can meet applications in wearable, adaptive camouflage and other fields. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 TG curve of the polyurethane solid electrolyte prepared in Example 1;
[0040] Figure 2 is the DSC curve of the polyurethane solid electrolyte prepared in Example 1;
[0041] Figure 3 is the stress-strain curve of the polyurethane solid electrolyte prepared in Example 1;
[0042] Figure 4 is the adhesion of the polyurethane solid electrolyte prepared in Example 1;
[0043] Figure 5 is the infrared spectrum of the polyurethane solid electrolyte prepared in Example 2;
[0044] Figure 6 is the XRD curve of the polyurethane solid electrolyte prepared in Example 2;
[0045] Figure 7 is the response time of the electrochromic device prepared in Example 3;
[0046] Figure 8 is the cycle stability of the electrochromic device prepared in Example 3;
[0047] Fig. 9 is the bending cycle stability of the electrochromic device prepared in Example 3;
[0048] Fig.10 These are digital photos of the electrochromic fabric prepared in Example 3 in the faded and colored states.
[0049] Fig.11 This is a color change design diagram of the electrochromic fabric prepared in Example 4. DETAILED DESCRIPTION
[0050] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0051] Raw materials and reagents
[0052] Table 1 Main reagent names
[0053] Reagent name Molecular abbreviation Parameters / Indicators Manufacturer Polytetrahydrofuran PTMG AverageMn~850 Adamas Isophorone diisocyanate IPDI 99% Adamas Dibutyltin dilaurate DBTDL 95% TMstandard 2-Amino-2-methyl-1,3-propanediol AMPD 98% TCL N,N'-Dimethylacetamide DMAC 99.8% Adamas Lithium bis(trifluoromethanesulfonyl)imide LITFSI 98% Adamas
[0054] Testing and characterization of polyurethane solid electrolytes:
[0055] Thermogravimetric analysis (TG) was performed using a TG209 F1lris thermogravimetric analyzer. The temperature was raised from 50°C to 600°C in a nitrogen atmosphere at a heating rate of 10°C / min to obtain the thermal decomposition temperature of the material.
[0056] Differential Scanning Calorimetry (DSC) was performed using a DSC250 differential scanning calorimeter in a nitrogen atmosphere. The temperature was dropped from 80°C to -80°C, kept at 80°C and -80°C for 5 minutes, then raised to 80°C, then dropped to -80°C, and finally returned to room temperature. The temperature change rate was 10°C / min.
[0057] The stress-strain test was conducted using a WY-3020S-T2 universal specimen tensile machine. The specimen was dumbbell-shaped, and the specific test method was based on ASTM D624-2000 (2012) Standard Test Method for Tensile Properties of Vulcanized Rubber and Thermoplastic Elastomers. The test was conducted at a tensile speed of 50 mm / min, and the stress-strain curve was calculated using the formula.
[0058] The adhesion test was carried out using a YG(B)026G biomedical textile strength tester. The polymer was placed between two steel plates and rolled together using a hot press. The overlap area of the steel plates was 15*15mm, the clamping distance was 60mm, and the tensile speed was 50mm / min.
[0059] The Fourier transform infrared spectroscopy test uses an IS50 Fourier transform infrared spectrometer with a scanning range of 400-4000cm -1 X-ray diffraction (XRD) was performed using a Bruker D8 ADVANCE X-ray diffractometer to analyze the structure of the polyurethane solid electrolyte. The sample size was 1 cm*1 cm*1 cm, the test surface was flat, the equipment power was 2.2 KW, the minimum step size was 0.0001°, and the angle deviation was 0.01°.
[0060] Performance test of electrochromic unit:
[0061] The response time and bending cycle stability were tested by combining a CHI660E electrochemical workstation with a UV3600 Shimadzu UV spectrophotometer. The electrochemical workstation was used to apply a cyclic voltage, and the UV spectrophotometer recorded the change in reflectivity.
[0062] The cycling stability was tested by a CHI660E electrochemical workstation using a multi-potential step method, with voltage 1 set to 3 V for 10 s and voltage 2 set to -3 V for 10 s. The number of cycles was 600.
[0063] Example 1
[0064] The method for preparing the all-solid-state flexible stretchable electrochromic device in this embodiment comprises the following steps:
[0065] (1) 10g PTMG and 3.9872g LITFS were placed in a three-necked flask and dried under vacuum at 110℃ for one hour before reacting. Open the nitrogen, lower the system temperature to 80℃, take 2.10ml IPDI, 2-3 drops of DBTDL dissolved in 5ml DMAC, stir the mixture evenly and inject it into the reaction system, and continue the reaction for 5h. At 60℃, weigh 0.35g AMPD dissolved in 30ml DMAC and inject it into the reaction system, stir mechanically for 3h, continue to heat to 90℃, and continue stirring for 3h. Add an appropriate amount of DMAC by observing the change in the viscosity of the system, heat and remove DMAC after the reaction is completed, and finally obtain a polyurethane solid electrolyte.
[0066] (2) Heat the polyurethane solid electrolyte in step (1) to 80°C and then apply it on a 1 cm 2 The ITO-PET conductive surface is then bonded to another 1 cm2 thick film on which polyaniline or polythiophene has been deposited. 2 The electrochromic unit is obtained by repeating the above process to obtain multiple electrochromic units.
[0067] (3) 36 electrochromic units are integrated on the fabric using copper wires, and the electrochromic units and the fabric are bonded and fixed using the polyurethane solid electrolyte in step (1), thereby finally obtaining a fully solid-state flexible and stretchable electrochromic device.
[0068] The polyurethane solid electrolyte in the all-solid-state flexible stretchable electrochromic device prepared in this embodiment has good thermal stability. Figure 1-2 As shown, the thermal decomposition temperature is greater than 200 ° C, the glass transition temperature is -67 ° C, and the mechanical properties are good, and the tensile strain can reach 1250%. Figure 3 As shown. Figure 4 It can be seen that the electrolyte has excellent adhesion with an adhesion force of up to 260N.
[0069] Example 2
[0070] The method for preparing the all-solid-state flexible stretchable electrochromic device in this embodiment comprises the following steps:
[0071] (1) 10g PTMG and 3.0670g LITFS were placed in a three-necked flask and dried under vacuum at 110℃ for one hour before reacting. Open the nitrogen, lower the system temperature to 80℃, take 2.10ml IPDI, 2-3 drops of DBTDL dissolved in 5ml DMAC, stir the mixture evenly and inject it into the reaction system, and continue the reaction for 5h. At 60℃, weigh 0.35g AMPD dissolved in 30ml DMAC and inject it into the reaction system, stir mechanically for 3h, continue to heat to 90℃, and continue stirring for 3h. Add an appropriate amount of DMAC by observing the change in the viscosity of the system, heat and remove DMAC after the reaction is completed, and finally obtain a polyurethane solid electrolyte.
[0072] (2) Heat the polyurethane solid electrolyte in step (1) to 80°C and then apply it on a 1 cm 2 The ITO-PET conductive surface is then bonded to another 1 cm2 thick film on which polyaniline or polythiophene has been deposited. 2 The electrochromic unit is obtained by repeating the above process to obtain multiple electrochromic units.
[0073] (3) 36 electrochromic units are integrated on the fabric using copper wires, and the electrochromic units and the fabric are bonded and fixed using the polyurethane solid electrolyte in step (1), thereby finally obtaining a fully solid-state flexible and stretchable electrochromic device.
[0074] The polyurethane solid electrolyte in the all-solid-state flexible stretchable electrochromic device prepared in this example was characterized. Figure 5-6 As shown, an amorphous polymer electrolyte was successfully synthesized.
[0075] Example 3
[0076] The method for preparing the all-solid-state flexible stretchable electrochromic device in this embodiment comprises the following steps:
[0077] (1) 10g PTMG and 3.9872g LITFS were placed in a three-necked flask and dried under vacuum at 110℃ for one hour before reacting. Open the nitrogen, lower the system temperature to 80℃, take 2.10ml IPDI, 2-3 drops of DBTDL dissolved in 5ml DMAC, stir the mixture evenly and inject it into the reaction system, and continue the reaction for 5h. At 60℃, weigh 0.35g AMPD dissolved in 30ml DMAC and inject it into the reaction system, stir mechanically for 3h, continue to heat to 90℃, and continue stirring for 3h. Add an appropriate amount of DMAC by observing the change in the viscosity of the system, heat and remove DMAC after the reaction is completed, and finally obtain a polyurethane solid electrolyte.
[0078] (2) Heat the polyurethane solid electrolyte in step (1) to 100°C and then apply it on a 1 cm 2The ITO-PET conductive surface is then bonded to another 1 cm2 thick film on which polyaniline or polythiophene has been deposited. 2 The electrochromic unit is obtained by repeating the above process to obtain multiple electrochromic units.
[0079] (3) 36 electrochromic units are integrated on the fabric using copper wires, and the electrochromic units and the fabric are bonded and fixed using the polyurethane solid electrolyte in step (1), thereby finally obtaining a fully solid-state flexible and stretchable electrochromic device.
[0080] Depend on Figure 7 to Figure 9 As shown, the response time of the electrochromic device in this embodiment is less than 5 seconds, and it has good cycle stability and bending cycle stability. The electrochromic unit can continuously change color for 12,000 seconds, and bending 800 times does not affect the color change of the electrochromic unit. The electrochromic glove color change unit can be controlled independently, and the photos before and after electrochromic are shown in the figure below. Fig.10 shown.
[0081] Example 4
[0082] The method for preparing the all-solid-state flexible stretchable electrochromic device in this embodiment comprises the following steps:
[0083] (1) 10g PTMG and 3.9872g LITFS were placed in a three-necked flask and dried under vacuum at 110℃ for one hour before reacting. Open the nitrogen, lower the system temperature to 80℃, take 2.10ml IPDI, 2-3 drops of DBTDL dissolved in 5ml DMAC, stir the mixture evenly and inject it into the reaction system, and continue the reaction for 5h. At 60℃, weigh 0.35g AMPD dissolved in 30ml DMAC and inject it into the reaction system, stir mechanically for 3h, continue to heat to 90℃, and continue stirring for 3h. Add an appropriate amount of DMAC by observing the change in the viscosity of the system, heat and remove DMAC after the reaction is completed, and finally obtain a polyurethane solid electrolyte.
[0084] (2) Heat the polyurethane solid electrolyte in step (1) to 80°C and then apply it on a 2 cm 2 The ITO-PET conductive surface is then bonded to another 2 cm2 thick film on which polyaniline or polythiophene has been deposited. 2 The electrochromic unit is obtained by repeating the above process to obtain multiple electrochromic units.
[0085] (3) 36 electrochromic units are integrated on the fabric using copper wires, and the electrochromic units and the fabric are bonded and fixed using the polyurethane solid electrolyte in step (1). Finally, a fully solid-state flexible and stretchable electrochromic device is obtained. The arrangement order of the electrochromic units is designed according to the requirements, and a variety of color changes can be achieved by controlling the voltage applied to the electrochromic units. The color change design is as follows: Fig.11 shown.
[0086] Example 5
[0087] The method for preparing the all-solid-state flexible stretchable electrochromic device in this embodiment comprises the following steps:
[0088] (1) 10g PTMG and 3.9872g LITFS were placed in a three-necked flask and dried under vacuum at 110℃ for one hour before reacting. Open the nitrogen, lower the system temperature to 80℃, take 2.10ml IPDI, 2-3 drops of DBTDL dissolved in 5ml DMAC, stir the mixture evenly and inject it into the reaction system, and continue the reaction for 5h. At 60℃, weigh 0.35g AMPD dissolved in 30ml DMAC and inject it into the reaction system, stir mechanically for 3h, continue to heat to 90℃, and continue stirring for 3h. Add an appropriate amount of DMAC by observing the change in the viscosity of the system, heat and remove DMAC after the reaction is completed, and finally obtain a polyurethane solid electrolyte.
[0089] (2) Heat the polyurethane solid electrolyte in step (1) to 80°C and then apply it on a 2 cm 2 The ITO-PET conductive surface is then bonded to another 2 cm2 thick film on which polyaniline or polythiophene has been deposited. 2 The electrochromic unit is obtained by repeating the above process to obtain multiple electrochromic units.
[0090] (3) 49 electrochromic units are integrated on the fabric using copper wires, and the electrochromic units and the fabric are bonded and fixed using the polyurethane solid electrolyte in step (1), thereby finally obtaining a fully solid-state flexible and stretchable electrochromic device.
Claims
1. A method for preparing a solid electrolyte, comprising: (1) mixing a diisocyanate, a catalyst, and an organic solvent to obtain a mixed solution; (2) mixing the mixed solution of step (1), polyol and lithium salt, and reacting them to obtain a prepolymer; (3) A chain extender is added to the prepolymer of step (2) to react, and then the solvent is removed to obtain a solid electrolyte.
2. The preparation method according to claim 1, characterized in that: In step (1), the diisocyanate is one or more of isophorone diisocyanate and hexamethylene diisocyanate; the catalyst is dibutyltin dilaurate; and the organic solvent is N,N'-dimethylacetamide; The catalyst accounts for 0.1 wt% to 0.9 wt% of the total weight of the monomers.
3. The preparation method according to claim 1, characterized in that: In step (2), the polyol is one or more of polytetrahydrofuran, polyethylene glycol, and polyethylene oxide; the lithium salt is one or more of lithium bis(trifluoromethylsulfonyl)imide, lithium difluoromethylsulfonylimide, and lithium perchlorate; The molar ratio of the polyol to the diisocyanate is 1:(1-4); the content of the lithium salt is 20wt%-60wt% of the total weight of the monomers; in the step (2), the polyol and the lithium salt are pre-treated, wherein the pre-treatment is vacuum drying to remove moisture.
4. The preparation method according to claim 1, characterized in that: The structural formula of the chain extender in step (3) is: Wherein R1 and R2 are selected from one or more of amino, carbonyl, carboxyl, and Upy; The molar ratio of polyol to chain extender is 1:(1-4).
5. The preparation method according to claim 1, characterized in that: In step (2), the reaction is carried out under protective gas conditions at 50-90° C. with stirring for 2-5 hours; The reaction in step (3) is as follows: stirring at 40-60°C for 2-5 hours, then heating to 80-90°C and stirring for 3-6 hours.
6. An electrochromic device, characterized in that: The electrochromic device comprises an electrochromic unit, a solid electrolyte prepared by the method of claim 1, and a fabric substrate; wherein the solid electrolyte is arranged between the electrochromic unit and the fabric substrate.
7. The electrochromic device according to claim 6, characterized in that: The electrochromic unit comprises in sequence a transparent conductive layer, an electrochromic layer, a solid electrolyte layer prepared by the method of claim 1, and a transparent counter electrode layer; the multiple electrochromic units are connected by conductors and integrated on the surface of the substrate.
8. The electrochromic device according to claim 6, characterized in that: The electrochromic layer is one or more of polythiophene, polyaniline and polypyrrole; the electrochromic unit area is 1-9cm 2 .
9. A method for preparing an electrochromic device, comprising: The electrochromic unit, solid electrolyte and fabric are stacked and then hot pressed to obtain it.
10. Application of the electrochromic device according to claim 6 in the fields of wearable, information display and adaptive camouflage.
Citation Information
Patent Citations
Flexible hot melt adhesive-type all-solid-state flexible electrochromic device
CN109270761A
Polyurethanes Having Good Hydrophilic andIon-conductive Properties and Method for PreparingThereof
KR1020020010251A
Stretchable devices and methods of manufacture and use thereof
US20120224247A1